2018
DOI: 10.1021/acs.jmedchem.8b00198
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Cleavage of a Tripeptide Linkage by Enzymes on Renal Brush Border Membrane To Reduce Renal Radioactivity Levels of Radiolabeled Antibody Fragments

Abstract: The obstructive renal radioactivity after injection of antibody fragments/constructs labeled with metallic radionuclides would be improved by liberating a radiometal chelate of urinary excretion from the antibody molecules by enzymes on the renal brush border membrane (BBM). A tripeptide GFK sequence was newly evaluated as an enzyme-cleavable linkage and conjugated to a Tc chelate of an isonicotinic acid derivative of 2-picolylglycine (Tc-IPG). Tc-IPG-glycine was liberated fromTc-IPG-GFK by the enzymes, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…In contrast, the accumulation of [ 68 Ga]Ac-CG6 in the kidneys remained at a level greater than 75 %ID/g at 2 h post-injection. Therefore, further structural modification, such as the incorporation of renal brush border enzyme-cleavable linkers, 34 will be required to reduce the renal retention of [ 68 Ga]Ac-CG6.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the accumulation of [ 68 Ga]Ac-CG6 in the kidneys remained at a level greater than 75 %ID/g at 2 h post-injection. Therefore, further structural modification, such as the incorporation of renal brush border enzyme-cleavable linkers, 34 will be required to reduce the renal retention of [ 68 Ga]Ac-CG6.…”
Section: Discussionmentioning
confidence: 99%
“…A study has demonstrated that derivatives of [ 68 Ga]Ga-DOTA-AmBz-MVK-OH could be cleaved specifically by neutral endopeptidase (NEP), and therefore, the amino acids linker MVK could reduce kidney uptake of radiolabeled DOTA-conjugated peptides and peptidomimetics [133]. These findings would allow to develop radiometal-based radiopharmaceuticals with clinically relevant lower renal radioactivity levels [134].…”
Section: Future Perspectives Of 213 Bi-tatmentioning
confidence: 99%
“…1819 Incorporation of renal brush border enzyme (BBE)-cleavable linkers such as glycine-lysine (GK) or glycine-tyrosine dipeptide between the radiolabeled moiety and the targeting vector significantly reduced renal activity levels from radiolabeled antibody fragments without concomitant reduction in their tumor uptake. 2021…”
Section: Introductionmentioning
confidence: 99%
“…High and persistent localization of activity from radiolabeled peptides and low molecular weight antibody fragments in the kidneys has been attributed to several factors. These include electrostatic interaction between the negatively charged proximal tubular cell surface and positively charged molecules and endocytosis mediated by receptors such as megalin and cubulin. Strategies to reduce renal accumulation of activity by countering these factors have included administration of basic amino acids and the plasma expander gelofusine, increasing the negative charge of the labeled entity via chemical modification, and insertion of cleavable linkers. , Incorporation of renal brush border enzyme (BBE)-cleavable linkers such as glycine-lysine (GK) or glycine-tyrosine dipeptide between the radiolabeled moiety and the targeting vector significantly reduced renal activity levels from radiolabeled antibody fragments without concomitant reduction in their tumor uptake. , …”
Section: Introductionmentioning
confidence: 99%